Laddering the benefit-link-value of premium products: perception of Indian consumers on consumer packaged goods. (2016) - Natarajan, Subhashree; Abdullah, T.K.T. Sheikh; Deepa, M.
The word 'premium' can conjure a plethora of meaning that includes quality, cost, convenience and many more; it varies with segment and product category. The rapid growth of specialty gourmet stores and e-tailing hubs pose a greater challenge in understanding the word 'premium as-perceived-by consumers'. This study explores the perception of consumers towards the so-called premium products; what according to conservative consumers is the real 'premiumness'? The study also attempts to classify the value proposition of consumers towards the premium consumer packaged products as hedonic and utilitarian benefits, across organic and natural shelves of many retail channels and banners, in the conservative markets of India, by laddering the benefit links to values. Purposive sampling for in-depth interview of 60 respondents drawn from three strata with two economic classes is adopted. The study reveals that the high-income group regularly buys premium products but the premium product purchase growth and aspirational effects are stronger in low-income group. The outcome of the study is expected to help the marketers define every variable in the value equation of CPG premium products, according to the customer category.